Structural Balancing vs Horizon Flattening on Seismic Data: Example from Extensional Tectonic Setting. (30th January 2015) - Jamaludin, S N Fathiyah; Latiff, A H Abdul; Ghosh, D P
Abstract: Two techniques which are structural balancing and horizon flattening have been applied in this work to verify and validate the seismic interpretation performed on a few extracted 2D seismic cross-sections. Both techniques are useful to provide a mean of understanding what had happened or at least to imagine what had happened during the time of deposition for each of the interpreted horizons. Structural balancing technique is somehow more difficult, time-consuming and requires other information such as rocks' densities before it can be practiced. Horizon flattening, on the other hand is a straight-forward technique available in most interpretation software. Comparing the results from both techniques had shown us that structural balancing, despite its difficulties and time-consuming had provided a more geologically sound interpretation. It allows the interpreters to understand and imagine the relationship of faulting with sedimentation at a particular time. However, horizon flattening only provides a general overview on the morphology and environment of deposition for the flattened horizons. Despite all, both techniques require a familiarity with the interpretation and structural software and what is important is an interpreter who can make his or her interpretation geologically acceptable and logic.